2015
DOI: 10.1002/pbc.25711
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Stem Cell Transplantation for CD40 Ligand Deficiency: Single Institution Experience

Abstract: Allogeneic HSCT results in excellent survival and sustained immune reconstitution in patients with CD40 ligand deficiency using both myeloablative and reduced intensity conditioning approaches and various graft sources, including bone marrow, peripheral blood, and umbilical cord blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 37 publications
1
8
0
1
Order By: Relevance
“…While the only corrective treatment for HIGM is HSCT, long term data remain limited [8, 29, 30]. The USIDNET Registry currently contains limited information on 13 transplanted subjects.…”
Section: Discussionmentioning
confidence: 99%
“…While the only corrective treatment for HIGM is HSCT, long term data remain limited [8, 29, 30]. The USIDNET Registry currently contains limited information on 13 transplanted subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to previously reported results, this suggests that complications, rather than immune reconstitution, present the main problem after HSCT in patients with CD40L‐deficiency 5,8,9 . In view of such promising results, HSCT for patients with CD40L‐deficiency has been increasingly attempted and proven successful, as reported in single‐center experience reports, which provide important case studies for future research on broad cohorts of patients 4‐11 . However, negative results in larger cohorts of patients suggest that transplantations with poor prognosis have not been reported.…”
Section: Discussionmentioning
confidence: 66%
“…We, therefore, found the lowest reported GVHD rate among patients with CD40L‐deficiency. This is attributable to the effects of ATG use, promptly administered HSCTs, the pretransplant conditioning of our patients, and the consequent low risk of toxicity 4‐11 . To our knowledge, haploidentical HSCT performed in twins with unmanipulated bone marrow and GVHD prophylaxis with cyclophosphamide post‐transplant has not previously been reported.…”
Section: Discussionmentioning
confidence: 93%
“…HSCT was considered late in the course of CVID when markedly end-organ damage appeared. Previous studies demonstrated that early HSCT prior to end organ damage considerably improves HSCT outcomes [83].…”
Section: Immunoglobulin Replacement Therapy ; a Shot For Prevention Omentioning
confidence: 99%